PENGELOLAAN KEBISINGAN DI JALAN RAYA CANGGU, DESA CANGGU, KECAMATAN KUTA UTARA, KABUPATEN BADUNG, PROVINSI BALI - Cahyaninghati, Ni Made Ruth; Paturusi, Syamsul Alam; Antara, Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2024)
Noise is a disturbing sound that occurs and causes an uncomfortable feeling for the listener. The density of tourism in Canggu creates an uncomfortable feeling for the local community, due to the noise generated by tourism activities and other activities. Therefore, the purpose of this research is determine the level of noise that occurs on Jalan Raya Canggu as well as determine the community's response to disturbance and provide strategies for dealing with noise. This research was carried out by collecting information regarding noise levels through observations and questionnaires on Jalan Raya Canggu. The total number of respondents taken was 30 respondents. Noise levels are calculated using a formula based on Minister  of Environment Decree Number 48 of 1996 using a sound level meter. Community disturbance scores are processed using a Likert scale. The research results show that based on 5 research points the highest noise peak is at 09.00 and the lowest noise is at 01.00. The response to community disturbance with the highest index value was community disturbance due to traffic density, namely 89.3%. SWOT analysis is used to obtain noise management strategies on Jalan Raya Canggu. Jalan Raya Canggu is located in quadrant IV (Defensive Strategy) with a strategy of maintaining the existing strength of Jalan Raya Canggu as a tourism route by improving traffic so that in the long term tourism development will increase and have a good effect on the community and reduce noise. Keywords: noise; community disturbance; traffic; management